Optimalisasi Sistem Pengelolaan E-Journal Berbasis Open Journal System (OJS) Menggunakan Framework CSS Bootstrap Pada Instansi dan Asosiasi - Handayani, Indri; Maulani, Giandari; Noviandri, Evira; Ningsih, Hesti Widya (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
A journal is a special article in articles in several fields of science. The journal is used as a reference in conducting scientific work both by students and by lecturers. At present several institutions and associations which are the object of research have used the OJS-based scientific journal processing and publication system. However, its publication is still based on OJS Version 2.4.8. In OJS Version 2.4.8, it's still not optimal, one of which is in terms of customization that can't adjust the display easily. Therefore, optimization of the e-journal management system is needed by using OJS Version 3.1.0.1 which is more flexible and has an attractive appearance and is easily customizable using the CSS Bootstrap Framework theme. The research methods in this study include the method of challenge analysis, the method of analyzing the need for system upgrade, and the method of software development using the waterfall method. After optimizing using OJS version 3.1.0.1, publications are easier to do and most importantly can be customized using the CSS Bootstrap Framework so that it is more user-friendly.